PRIORITAS CLUSTER PENGEMBANGAN PARIWISATA SEHAT DI KABUPATEN BANYUWANGI - Nur Anim Jauhariyah; Ahmad Munib Syafa’at (ICO EDUSHA, 2021)
The tourism sector is one of the drivers of economic growth in Banyuwangi Regency. This study aims to determine the priority of the cluster on the development of healthy tourism in Banyuwangi Regency. This study uses a mixed qualitative and quantitative method approach through interviews and distributing questionnaires to experts from the health office, culture and tourism office, and the Banyuwangi Regency Regional Development Planning Agency. The analysis technique uses the Analytic Network Process (ANP). The results of the analysis show that the priority of developing healthy tourism clusters in Banyuwangi Regency is Objects and Tourist Attractions by occupying the first position which indicates that DTW is a priority to be developed into healthy tourism with a percentage of 33%. Keywords: Healthy Tourism, Development, Sustainable, Banyuwangi Regency.